Hubungan Kemampuan Membaca Kritis dengan Kemampuan Menulis Argumentasi Siswa Kelas VIII SMPN 7 Pariaman - Ramadani, Putri Nur; Basri, Irfani; Emidar, Emidar (Universitas Negeri Padang, 2013)
The purposes of this study were to described of: (1) The critical reading ability, (2) The arguments writing ability, and (3) The relationships of the critical reading ability with the arguments writing ability the Grade VIII Junior High School 7 Pariaman. The type of this study was the corellative study by qualitative method. The population and sampling did by random sampling in 15 % from the population. According to the result of the data analyze and discussion it could be concluded as. First, the critical reading ability students of Grade VIII Junior High School 7 Pariaman was in the qualifying of more than enough (70,43). Second, the arguments writing ability students of Grade VIII Junior High School 7 Pariaman was in the qualifying of more than enogh (66). Third, there werw significant relationships between the criticalreading ability with the arguments writing ability the students of Grade VIII Junior High School 7 Pariaman on the independence degree n-2 at the 95 % of the significant stage.